Enhancement of Fodder Productivity through Melia based Silvipastoral System: - Kandasamy, Ramah (Indian Journal of Agroforestry, 2023)
A field experiment was conducted at Forest College and Research Station, Mettupalayam from 2017 to 2019 to estimate the productivity of fodder grasses and legume combination in the existing plantation of Melia dubia. Fodder crops viz., CO(BN)5 grass, Guinea grass CO(GG)3, Lucerne (Medicago sativa), Hedge lucerne (Desmanthus virgatus) and Stylosanthes were sown in two year old Melia plantation as sole crop and in combination. The trials were laid out in randomized block design and replicated thrice. Results of this experiment revealed that CO(BN)5 grass along with Hedge Lucerne were found to be compatible under Melia plantation in terms of fodder yield. In addition, the fodder crops grown as inter crops have a beneficial impact on the growth of tree component